(untitled) (Journal of Science and Technology, 2016)
The aim of this paper is to publicise the outcome of an experiment to create a new painting style called "Kente Simulation Painting”. The research into the creation of this new painting style or technique commenced in 1994, and was inspired by the nature and transitional character of the Asante Kente cloth. A painting to be made in this style requires an outline drawing of the subject matter first on the support. Vertical and horizontal brush strokes of colours are then painted over the drawing carefully to ensure that the outlines of the motifs drawn are not obliterated. This is followed with the tinting and shading of the lines and motifs at vantage parts. Textures are then introduced, to complete the painting. This new style or technique produces unique and exciting picturesque paintings. Although Piet Mondrian’s Geometric Abstraction also employs vertical and horizontal lines and shapes, the method of composition in the “Kente Simulation Painting” results in a touch of originality completely unlike Geometric Abstraction.